Cybernetic maps of the landscape: CAVS collaborative projects for the recovery of the natural environment of the Charles River - Lorenzo, Covadonga (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2020)
This article presents the projects that resulted from an institutional initiative, promoted by the Center for Advanced Visual Studies (CAVS) of the Massachusetts Institute of Technology (MIT) in the early seventies, in which a series of projects were proposed over the area of ​​the Charles River that explored the possibility of 'inhabiting' the river, understood as a physical boundary between the cities of Cambridge and Boston. The initiative raised the study of this area, then fragile and vulnerable, threatened by the uncontrolled growth of both cities and deeply deteriorated. In order to do that, the design of new urban spaces was proposed, based on the theory of systems and cybernetics, which used new technologies to transform the environment, proposing the recovery of the natural environment of the river to integrate it in continuity with the urban plot. All of them have had a strong impact on interactive architectures and intelligent environments that began to materialize in real proposals already in the eighties, less influenced by cybernetics than digital and which today are helping to visualize and raise awareness citizenship to prevent from negative parameters that could affect the urban environment in the context of current smart cities.
Keywords: Landscape; Technology; Cybernetics; Environment; Nature